Limiting business risks via limited liability partnerships (LLP); the Malaysian law and the Islamic law perspectives - Abd Ghadas, Zuhairah Ariff; Engku Ali, Engku Rabiah Adawiah (2009)
In all business, there will always be business risks, be it calculated or uncalculated risks. Other than finding the right investments or business, it is also important for businessmen to know the means to limit the liability in business. In such a matter, the choice of business vehicle is vital. At present, the Malaysian market place only offers sole proprietorships, partnerships and companies structure as options of business vehicles. However, in April 2008, the Companies Commission of Malaysia released the second consultative document on Malaysian limited liability partnerships (LLP). If the LLP is formally introduced in the market place, there will be a new business structure and a new business vehicle to limit business risk in Malaysia. It will also mark a major development in the Malaysian Partnerships Law. Under the Islamic law, partnerships structure (sharikah) has an established reputation and clear recognition as a valid business vehicle. The application of limited liability in sharikah is also well established and clearly justified. With the increasing number of Arab businessmen investing and doing business in Malaysia, it is important to look at the new LLP as one of the option of business vehicles. This paper intends to highlight features of the proposed LLP, with special reference to the attribute of limited liability. The discussion will include both the common law and the Islamic law perspectives.